Modeling and numerical simulation of fluid flow and heat transfer of a steel continuous casting tundish - Rocha, José Renê de Sousa (2017)
Currently, the continuous casting process is the most used technique to produce steel. Being an inherently component of the caster machine, the tundish has been designed to be not only an intermediate vessel between the ladle and the mold, but also a device to remove inclusions and a metallurgical reactor. Therefore, the tundish has an important role in the continuous casting process. The physical model for heat transfer and fluid flow into the tundish is very complex, thus analytical solutions are not available. Physical studies might present many difficulties for analyzing the process. Hence, Computational Fluid Dynamics (CFD) emerges as an attractive alternative. CFD is based on numerical approaches that are used to solve several classes of engineering problems. The main goal of the present study is to analyze the fluid flow and temperature fields into an actual tundish configuration that is used in continuous casting processes of a local steelmaker company. Based on the performed simulations, some modifications in the geometry of the tundish are proposed in order to improve the steel quality; these modifications make use of weirs and dams. For solving the governing equations arising from the physical model, the Ansys CFX software, which is based on the Element-based Finite-Volume Method (EbFVM) were used. Simulations were performed using water and steel as working fluids for a turbulent flow in a 3D tundish. The results were presented in terms of velocity and temperature fields and Residence Time Distribution (RTD) curves, which evaluated them qualitatively and quantitatively.